Analisis Biaya Berdasarkan Unit Cost pada Instalasi Rawat Inap - Nuryanggi Igusti; A Rizki Amelia; Arman Arman; Yusriani Yusriani; Suharni Suharni; A M Multazam; Nurmiati Muchlis (Rumah Sakit Ibnu Sina, Makassar, 2025)
Cost analysis serves as a critical tool for hospital management in evaluating the efficiency of resource utilization. One commonly employed method is unit cost analysis, which supports the assessment of service production processes, determination of break-even points, and formulation of strategic decisions related to service volume and cost control. This study aimed to analyze fixed costs, fixed operational (semi-variable) costs, variable operational costs, total costs, and unit costs in the Inpatient Unit of a Private Hospital in Makassar in 2023. This research adopted an operational research design with a descriptive quantitative approach. The population comprised all financial transactions at the hospital in 2023, with the sample including all transactions associated with inpatient services. The findings showed that the fixed cost amounted to IDR 5,216,229,922, fixed operational cost to IDR 2,811,580,099, and variable operational cost to IDR 3,727,281,560. Total costs, calculated using three different approaches, were IDR 2,915,361,139 (Total Cost I), IDR 1,136,844,781 (Total Cost II), and IDR 650,882,586 (Total Cost III). Unit costs based on the double distribution method were identified as follows: Super VIP – IDR 1,087,677; VIP – IDR 870,775; Class 1 – IDR 654,674; Class 2 – IDR 532,583; and Class 3 – IDR 330,577. The results indicated that unit costs exceeding service tariffs posed a risk of financial loss. Therefore, the study recommends the application of the Activity-Based Costing (ABC) method, the implementation of clinical pathways, and the development of superior service units. Hospitals are encouraged to conduct periodic unit cost analyses and to establish service tariffs rationally, grounded in the outcomes of cost calculations.